Simulação da nanoestruturação de nanofolhas de óxido de grafeno reduzido através de dinâmica molecular - Maria, Marco Aurélio Euflauzino [UNESP] (2015)
We studied the nanostructuration of reduced graphene oxide nanoplatelets wapped by the polymer poly (sodium4 styrenesulfonate) (GPSS), using compational simulation. A first step was taken for the study about formation of GPSS nanoplatelets, using coputational simulation, as we intend to study in a near future a self-assembled film of GPSS deposited onto Nafion® membranes. The motivation is a better comprehension of the blocking barrier mechanism to the passage of methanol and increasing the H+ ions conductivity observed experimentally in a direct methanol fuel cell setup made by Dra Celina M. Miyazaki (POSMAT, UNESP). We have made here the simulation of a reduced graphene oxide (rGO) nanoplatelet closer to that obtained experimentally, having defects (vacancies) and hydroxyl, epoxy, carboxyl and carbonyl chemical groups, resultant from the chemical synthesis. In addition, it was verified how rGO is surrounded by the PSS polymer, even in the presence of water, putting the system as close as possible to the experimental condition. The enveloping of rGO by PSS happened mainly by elestrostatic attraction between oxygen atoms present in PSS with hydrogen atoms present at hydroxyl and carbonyl groups in rGO, and it was favored by the presence of water. These observations are corroborated by the experimental results